Senator Obama goes to Africa [videorecording (DVD)] - Hercules, Bob; Obama, Barack (First Run Features, 2007)
Senator Barack Obama travels to the land of his ancestry. From South Africa to Kenya to a Darfur refugee camp in Chad, Obama explores the vast continent that is gaining increasing importance in this age of globalization.